Using Storytelling to Facilitate Change at the Workplace: Book Review - Taxner, Tünde (Filológia.hu, 2024)
Cleland Silva, Tricia – de Tarso Fonseca Silva, Paulo 2022: Making Sense of Work Through Collaborative Storytelling. Building Narratives in Organisational Change. Cham: Palgrave Macmillan. Online: https://doi.org/10.1007/978-3-030-89446-7